Recombinant matrix protein of Nipah virus - Tan, Wen Siang; Subramaniam, Senthil Kumar; Tey, Beng Ti; Hamid, Muhajir (2010)
The present invention provides a recombinant matrix protein of Nipah virus containing matrix protein of nipah virus which includes at least ine His tag and MYC epitope. Further, the present invention also provides a recombinant plasmid including recombinant matrix protein of Nipah virus. Also provided is a method for producing recombinant matrix protein of Nipah virus which includes the steps of (a) culturing expression vector of recombinant matrix protein in a medium which allows growth of the expression host, (b)allowing the recombinant matrix protein to be expressed in the expression host, (c) harvesting the expression host from step (b) from the medium, (d) disrupting the expression host harvested from step (c) in a medium for sonication purposes and (e) purifying the recombinant matrix protein obtained from step (d. Also provided is method for purifying recombinant matrix protein of Nipah virus which includes the steps of (a) harvesting and lysing recombinant expression host containing recombinant matrix protein cells, (b) purifying the recombinant matrix protein using nickel affinity column chromatography, (c) dialyzing the purified recombinant matrix protein from step (b) with buffer solution, (d)fractionating the purified recombinant matrix protein from step (c) using centrifugation and (e) collecting and poling the fractioned recombinant matrix protein obtained from step (d) concentration of protein. There is also provided a pharmaceutical composition comprising a therapeutically affective amount of recombinant matrix protein of Nipah virus. Also provided is a diagnostic reagent comprising an effective amount of recombinant matrix protein matrix of Nipah virus.